The Transformation of Sembah Batin Dance in the Development of Performing Arts in West Lampung Society - Nur Sintia; Pramutomo; Aris Setiawan (Gondang: Jurnal Seni dan Budaya, 2026)
This study aims to examine innovation in the Sembah Batin Dance as a form of performing arts development within the West Lampung community. The Sembah Batin Dance, created by Nyoman Mulyawan in 2010, now functions as a welcoming dance for guests at various official events, traditional ceremonies, and wedding processions. The uniqueness of this dance lies in its ability to adapt to modern social contexts through innovations in movement forms, accompanying music, and presentation structure, without abandoning noble values ​​such as respect, mutual cooperation, and togetherness. This research employs an ethnocoreological approach to analyze aspects of meaning as well as elements of choreography, costumes, properties, and music. The findings indicate that innovation in the Sembah Batin Dance plays an important role in maintaining the sustainability of tradition and strengthening the existence of regional performing arts amid the social dynamics of West Lampung.